Stargirl - Spinelli, Jerry (New York : A. Knopf : Distributed by Random House, 2000)
Stargirl, a teen who animates quiet Mica High with her colorful personality, suddenly finds herself shunned for her refusal to conform.
Wilson's Senior High School, November 2002.
Wilson's Junior High School, January 2010.
Notable/Best Books (A.L.A.), January 2001.
School Library Journal, August 2000.
Book Links (A.L.A.), September 2006.
Books for the Teen Age (NYPL), May 2002.
Keywords: Individuality -- Juvenile fiction; Popularity -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Individuality -- Fiction; Popularity -- Fiction; Eccentrics and eccentricities -- Fiction; High schools -- Fiction; Schools -- Fiction; Individuality -- Fiction; Popularity -- Fiction; Eccentrics and eccentricities -- Fiction; High schools -- Fiction; School stories; Individuality -- Fiction; Popularity -- Fiction; High schools -- Fiction; Love -- Fiction; Arizona -- Juvenile fiction; Arizona -- Fiction; Arizona -- Fiction; Arizona -- Fiction